Educational psychology - Santrock, John W. (McGraw-Hill, 2008)
Written by the author of highly effective psychology texts relied upon by thousands of teachers and students, Educational Psychology is a well-crafted text that emphasizes the application of theory to classroom practice. With richly evocative classroom vignettes provided by practicing teachers, as well as the most case studies - three per chapter - of any Introductory text, Santrock's Educational Psychology helps students think critically about the research basis for best practices. Additionally, Santrock's hallmark Learning System organizes the content into manageable chunks to support retention and mastery and making it much more likely that students will have an engaging and successful course experience.